Automating M-mode echocardiographic measurements for enhanced image analysis - Baldelomar, Lynzle T.; Nacu, Lester A.; Reyes, Maria Charlene F. (2011.)
This research explore a new approach in automating the analysis of m-mode images from echocardiographic examination video using a system of low-level image processing techniques. M-mode echocardiographic measurements are done manually according to the recommendation of the American Society of the Echocardiography. The accuracy of the measurements done in the m-mode highly depends on the operator. the inherent noise to echocardiogram and deformable characteristic of t5he structures add more to the complexity of the problem and variability of the measurements. A fast and ccaurate method for analyzing m-mode images is developed in this paper to facilitate the manual analysis. The system selects frames containing m-mode from th video using template matching and segregates data such as the m-mode, Electrocardiograph (ECG), measurement scales, into different dimensions. ECG is used to locate regions of the m-mode where measurements are taken with respect to time. Cardiac structures are then segmented into regions by thresholding.
With user manual (bound with the main text).
Thesis (B.S. Computer Science)--University of the Philippines, Diliman.
Keywords: Echocardiography; Image analysis; Image processing -- Digital techniques